The remainder when f(x) = x³ - 2x² - 5x + 16 is divided by (x+3) is -14
The functions are given as
f(x)=x^3-2x^2-5x+16 is divided by (x+3)
Rewrite them as
f(x) = x³ - 2x² - 5x + 16 is divided by (x+3)
Set the divisor to 0
So, we have
x + 3 = 0
Determine the value of x
This gives
x = -3
Substitute x = -3 in the function f(x)
So, we have
f(-3) = (-3)³ - 2(-3)² - 5(-3) + 16
Evaluate the expression
f(-3) = -14
By the remainder theorem, this represents the remainder
Read more about remainder at
https://brainly.com/question/14130807
#SPJ1